Performance of Fast Repetition Rate fluorometry based estimates of primary productivity in coastal waters - Robinson, Charlotte; Suggett, D.; Cherukuru, N.; Ralph, P.; Doblin, M. (Elsevier, 2014)
Capturing the variability of primary productivity in highly dynamic coastal ecosystems remains a major challenge to marine scientists. To test the suitability of Fast Repetition Rate fluorometry (FRRf) for rapid assessment of primary productivity in estuarine and coastal locations, we conducted a series of paired analyses estimating 14C carbon fixation and primary productivity from electron transport rates with a Fast Repetition Rate fluorometer MkII, from waters on the Australian east coast. Samples were collected from two locations with contrasting optical properties and we compared the relative magnitude of photosynthetic traits, such as the maximum rate of photosynthesis (Pmax), light utilisation efficiency (α) and minimum saturating irradiance (EK) estimated using both methods. In the case of FRRf, we applied recent algorithm developments that enabled electron transport rates to be determined free from the need for assumed constants, as in most previous studies. Differences in the concentration and relative proportion of optically active substances at the two locations were evident in the contrasting attenuation of PAR (400–700 nm), blue (431 nm), green (531 nm) and red (669 nm) wavelengths. FRRF-derived estimates of photosynthetic parameters were positively correlated with independent estimates of 14C carbon fixation (Pmax: n = 19, R2 = 0.66; α: n = 21, R2 = 0.77; EK: n = 19, R2 = 0.45; all p < 0.05), however primary productivity was frequently underestimated by the FRRf method. Up to 81% of the variation in the relationship between FRRf and 14C estimates was explained by the presence of pico-cyanobacteria and chlorophyll-a biomass, and the proportion of photoprotective pigments, that appeared to be linked to turbidity. We discuss the potential importance of cyanobacteria in influencing the underestimations of FRRf productivity and steps to overcome this potential limitation.